Award Winner in the Young Investigator Category, 2014 Society for Biomaterials Annual Meeting and Exposition, Denver, Colorado, April 16–19, 2014: Periodically perforated core–shell collagen biomaterials balance cell infiltration, bioactivity, and mechanical properties. Issue 4 (31st December 2013) - Caliari, Steven R.; Mozdzen, Laura C.; Armitage, Oliver; Oyen, Michelle L.; Harley, Brendan A. C.
Abstract Orthopedic tissue engineering requires biomaterials with robust mechanics as well as adequate porosity and permeability to support cell motility, proliferation, and new extracellular matrix (ECM) synthesis. While collagen–glycosaminoglycan (CG) scaffolds have been developed for a range of tissue engineering applications, they exhibit poor mechanical properties. Building on previous work in our lab that described composite CG biomaterials containing a porous scaffold core and nonporous CG membrane shell inspired by mechanically efficient core–shell composites in nature, this study explores an approach to improve cellular infiltration and metabolic health within these core–shell composites. We use indentation analyses to demonstrate that CG membranes, while less permeable than porous CG scaffolds, show similar permeability to dense materials such as small intestine submucosa (SIS). We also describe a simple method to fabricate CG membranes with organized arrays of microscale perforations. We demonstrate that perforated membranes support improved tenocyte migration into CG scaffolds, and that migration is enhanced by platelet‐derived growth factor BB‐mediated chemotaxis. CG core–shell composites fabricated with perforated membranes display scaffold‐membrane integration with significantly improved tensile properties compared to scaffolds without membrane shells. Finally, we show that perforated membrane‐scaffold composites support sustained tenocyte metabolic activity as well as improved cell infiltration and reduced expression of hypoxia‐inducible factor 1α compared to composites with nonperforated membranes. These results will guide the design of improved biomaterials for tendon repair that are mechanically competent while also supporting infiltration of exogenous cells and other extrinsic mediators of wound healing. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 917–927, 2014.